2008
DOI: 10.1590/s0100-40422008000400020
|View full text |Cite
|
Sign up to set email alerts
|

Bioreduction of substituted a-tetralones promoted by Daucus carota root

Abstract: Recebido em 15/1/08; aceito em 27/2/08; publicado na web em 2/4/09The bioreduction of a series of substituted α-tetralones, carried out using Daucus carota root (carrot), afforded the corresponding homochiral α-tetralols in variable conversions (9 to 90%) and excellent enantiomeric excesses. Two of the assayed α-tetralones were resistant to the bioreduction conditions. The absolute configurations of four α-tetralols were assigned as being (S), by comparison to the (S)-enantiomers obtained by kinetic resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In our laboratory we have researched the biocatalytic diversity of endophytic microorganisms (bacteria, yeast and fungi) in order to identify newer biocatalysts and also to enlighten the interesting phenomena of the stereoselective reduction of ketones by simple plants fragments. These type of enzymatic transformations were originally reported by Mironowicz [9] and Baldassarre [10] at the end of the XX century and several other reports have followed studying the scope and limitations of the reactions [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 90%
“…In our laboratory we have researched the biocatalytic diversity of endophytic microorganisms (bacteria, yeast and fungi) in order to identify newer biocatalysts and also to enlighten the interesting phenomena of the stereoselective reduction of ketones by simple plants fragments. These type of enzymatic transformations were originally reported by Mironowicz [9] and Baldassarre [10] at the end of the XX century and several other reports have followed studying the scope and limitations of the reactions [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, Yadav et al reported that Daucus carota exhibited good performance in the asymmetric reduction of 1 to ( S )‐2 in terms of enantioselectivity (96% ee), but low conversion (70%) and yield (52%) 21 . In another study performed with D. carota cell biocatalyst, it was reported that ( S )‐2 was obtained with 88% conversion and 95% ee 22 . In another study in the literature, it was reported that in the presence of Didymosphaeria igniaria whole‐cell biocatalyst, the asymmetric reduction of 1 to ( S )‐2 was achieved with 71% yield and 78% ee 23 .…”
Section: Introductionmentioning
confidence: 89%
“…Different natural materials are used as solid support as well as catalysts in a large number of reactions promoting the formation of final products. Natural materials such as different plant parts such as fruits, root extracts [26][27][28][29][30][31][32], clays [33,34], zeolites [35,36] and enzymes [37,38] are used effectively in numerous chemical transformations.…”
Section: Introductionmentioning
confidence: 99%